Estudio de la tipología monetaria como documento propagandístico de la evolución política española (1975-2003) - Francisco Olmos, José María de (Revista General de Información y Documentación, 2006)
Monetary types and legends have always been one of the main means of propaganda in the hands of the established power, and its importance is increased when transcendental changes take place, as happened in Spain from 1975. In this item our purpose is to demonstrate how the peseta became a first magnitude political document to show the evolution of the political Spanish system, not only in the so called Transition, but also in the subsequent periods up to its disappearance within the monetary policy of the European Union. We shall see the decisive moments when the peseta shows the political continuity and then the changes towards democratization and the acceptance of the new constitutional symbols, and finally the support of the autonomies state giving the priority to the common values, specially the cultural ones.
Keywords: Numismatics; Political propaganda; Spanish Transition; Juan Carlos I’ reign; Franco’s regime